2015
DOI: 10.1093/mnras/stv1216
|View full text |Cite
|
Sign up to set email alerts
|

Sco X-1 revisited withKepler, MAXI and HERMES: outflows, time-lags and echoes unveiled

Abstract: Sco X-1 has been the subject of many multi-wavelength studies in the past, being the brightest persistent extra-solar X-ray source ever observed. Here we revisit Sco X-1 with simultaneous short cadence Kepler optical photometry and MAXI X-ray photometry over a 78 day period, as well as optical spectroscopy obtained with HERMES. We find Sco X-1 to be highly variable in all our datasets. The optical fluxes are clearly bimodal, implying the system can be found in two distinct optical states. These states are gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…We extracted light curves for 17 systems from this sample that did not have neighbors close by in the target pixel files provided by the Mikulski Archive for Space Telescopes (MAST). This allowed us to create light curves using relatively large target and background masks, which mitigated the effect of spacecraft jitter in the resulting light curves (41). We visually identified 6 of these 17 light curves as displaying clear aperiodic variability.…”
Section: Sample Selectionmentioning
confidence: 99%
“…We extracted light curves for 17 systems from this sample that did not have neighbors close by in the target pixel files provided by the Mikulski Archive for Space Telescopes (MAST). This allowed us to create light curves using relatively large target and background masks, which mitigated the effect of spacecraft jitter in the resulting light curves (41). We visually identified 6 of these 17 light curves as displaying clear aperiodic variability.…”
Section: Sample Selectionmentioning
confidence: 99%
“…This has already been extensively discussed by Scaringi et al (2015) and attributed to a thermal time-scale lag. These authors reinforce its significance by de- Figure 14.…”
Section: Time Delaysmentioning
confidence: 59%
“…These asymmetries presumably arise from the intrinsic asymmetry of the failed transitions (brightenings in the low state and dips in the high state.) Scaringi et al (2015) used MAXI colours to identify FB and NB epochs. They found that the high state was usually associated with the FB and that the low state corresponded to the NB.…”
Section: Detrended Light Curvesmentioning
confidence: 99%
“…A regular optical variability of Sco X-1 with a period ≈ 18.9 h was discovered using archival photographic plates by Gottlieb et al (1975) and was confirmed using spectroscopic observations (Cowley & Crampton 1975). Scaringi et al (2015); Hakala et al (2015); Hynes et al (2016) conducted the analysis of optical observations of Sco X-1 obtained by Kepler K2 mission and of X-ray observations obtained by Fermi GBM and MAXI. An average wavelength of wide wavelength range observations of Kepler K2 mission was in the middle of a band that corresponded to B, V, R filters.…”
Section: Inroductionmentioning
confidence: 84%